Association between HOMA-IR with ketoacidosis and lipid profile markers in diabetic nephropathy patients - Zrar Saleem Kareem Almarzany (Zanco Journal of Pure and Applied Sciences, 2021)
The study designed to study the relationship between the homeostatic model assessment of insulin resistance (HOMA-IR) with ketoacidosis markers and hyperlipidemia in patients with non-insulin-dependent diabetes mellitus (NIDDM) and chronic kidney disease at end-stage renal disease (ESRD). Disturbance of the mechanisms which maintain normal blood pH and lipid profiles is a defining feature of chronic metabolic diseases such as diabetes and kidney failure. The present research included 90 patients and 30 healthy subjects. Serum insulin, fasting blood sugar (FBS), glycated hemoglobin % (HbA1c %) and HOMA-IR levels, lipid profile parameters and ketoacidosis markers were estimated in all groups. Statistical analysis showed that high HOMA-IR was significantly associated with lipid profiles and ketoacidosis markers in patients' groups when compared with control. Receiver operating characteristic (ROC) curve analysis investigated HOMA-IR as a significant risk factor for diabetic nephropathy (DN) in ESRD patients. The present finding regarding ROC curve analysis observed that IR is dependently associated with ketoacidosis and lipid profile abnormalities in NIDDM, ESRD and DN patients. Also, the study suggested HOMA-IR as a consequence and risk factor in DN at ESRD.